2022
DOI: 10.1186/s12903-022-02046-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of dental implant placement with computer-guided surgery: a retrospective cohort study

Abstract: Background The aim of this study was to assess the accuracy of virtual planning of computer-guided surgery based on the actual outcomes of clinical dental implant placement. Methods This retrospective study enrolled patients among whom implant treatment was planned using computer-guided surgery with cone beam computed tomography (CBCT). The patients who received implant according to the guide with the flapless and flapped approach were classifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
9
0
4
Order By: Relevance
“…Im klinischen Alltag bedeutet dies bei der konventionellen Implantatchirurgie ein invasiveres chirurgisches Vorgehen, da Strukturen dargestellt werden müssen, um die morphologischen Verhältnisse klinisch besser abschätzen zu können [33]. Ein ausgedehnter Operationsumfang ist aber mit Blick auf die beschriebene Wundheilungsproblematik bei bestrahlten Patienten grundsätzlich zu vermeiden [34].…”
Section: Bewertung Der Digitalen Planung Zur Implantologischen Defekt...unclassified
See 1 more Smart Citation
“…Im klinischen Alltag bedeutet dies bei der konventionellen Implantatchirurgie ein invasiveres chirurgisches Vorgehen, da Strukturen dargestellt werden müssen, um die morphologischen Verhältnisse klinisch besser abschätzen zu können [33]. Ein ausgedehnter Operationsumfang ist aber mit Blick auf die beschriebene Wundheilungsproblematik bei bestrahlten Patienten grundsätzlich zu vermeiden [34].…”
Section: Bewertung Der Digitalen Planung Zur Implantologischen Defekt...unclassified
“…Mit Blick auf die umfangreiche Methodik der digitalen Implantatchirurgie belegt die Literatur signifikant präzisere und akkuratere Implantationsergebnisse bei gesunden Patienten [27,32,33]. Die vertikale Deviation bei der digitalen Implantatchirurgie betrug durchschnittlich 0,19 mm mit einer maximalen Abweichung von 0,44 mm [32].…”
Section: Merkeunclassified
“…Although several studies have demonstrated the accuracy of CAS technology in dental implant surgery and have claimed the superiority of this approach over traditional techniques, to date, only a meta-analysis has been published reporting on the comparison of computer-assisted technology to the conventional freehand technique and found no significant differences between the two approaches for marginal bone loss, mechanical and biological complications and implant survival rate [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, these results should be interpreted with caution given the lack of homogeneity that limited this systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These 3-in-1 systems are principally capable of covering a wide range of imaging tasks. For instance, broad applications have already been reported for head-neck surgery, 1 maxillofacial surgery, 5,6 dentistry, 7,8 and radiotherapy. [9][10][11][12] To ensure performance stability in clinical operation, conducting technical quality assurance (QA) is essential.…”
Section: Introductionmentioning
confidence: 99%